Adverse events: objective or by consensus? - Cárcamo Quezada, César (Acta Bioethica, 2012)
An adverse event is not an objective problem, since its measure or quantification does not constitute the problem as a field with explanations and statements, but the application of shared validation criteria of causal explanations by a community of observers in their experience. We propose that an adverse event is a problem only if we can distinguish it by consensus, therefore, it is a social construction. The critical question is not where to trace the limit, but who can do it. Different interpretations of the same incident are always possible. In fact, when putting objectivity in hold we realize that reality is specified by an operation of distinction and that there are so many reality fields as types of operation of distinction. As a result, the objective facts disappear and we cannot pretend that we have a privilege access to an objective reality that we can use to validate our statements, being liberated to build a culture that does not look behind trying to find who is right, but rather to look ahead such as changing towards acting based on an ethics of responsibility.